Polynomial inequalities in regions with interior zero angles in the Bergman space - Abdullayev, F. G.; Balci, S.; Imash, kyzy M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We investigate the order of growth of the moduli of arbitrary algebraic polynomials in the weighted Bergman space A_p(G, h), p > 0, in regions with interior zero angles at finitely many boundary points. We obtain estimations for algebraic polynomials in bounded regions with piecewise smooth boundary.